2019
DOI: 10.36380/scil.2019.ojafr29
|View full text |Cite
|
Sign up to set email alerts
|

The effects of different litter material on broiler performance and feet health.

Abstract: The study was implemented at the National University of Lesotho with the aim to find a potential litter material for use in broiler production. The study followed a completely randomized design with four litter treatments replicated three times. A well ventilated house divided into 12 pans was used where each pan or a replicate contain 15 birds with a total of (n=180) birds. Feeding and watering were done on ad libitum basis while the normal routine for broiler production was followed. Litter treatments were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 9 publications
(10 reference statements)
6
20
1
Order By: Relevance
“…This nding is probably because of the differences in the quality of the litter types. Similar to our result, the birds raised on sand litter had healthier FPD than those raised on wheat and bean straw litters (Bilgili et al, 1999;Balabel, 2005 andKuleile et al, 2019). Also, Ferrante et al, (2006) reported that feather scoring and footpad lesions were negatively affected by straw litter compared to wood shavings and sand.…”
Section: Welfare and Behavioral Patternssupporting
confidence: 87%
See 4 more Smart Citations
“…This nding is probably because of the differences in the quality of the litter types. Similar to our result, the birds raised on sand litter had healthier FPD than those raised on wheat and bean straw litters (Bilgili et al, 1999;Balabel, 2005 andKuleile et al, 2019). Also, Ferrante et al, (2006) reported that feather scoring and footpad lesions were negatively affected by straw litter compared to wood shavings and sand.…”
Section: Welfare and Behavioral Patternssupporting
confidence: 87%
“…The ndings of our study are in full agreement with the ndings of Gernat (2009), who declared that sand had the lowest temperatures that positively affected bird's body temperatures, particularly under summer season. Also, Kuleile et al, (2019) found that body temperature of the birds raised on wood shavings litter increased gradually while those reared on sand recorded lower body temperature than of all studied litter materials.…”
Section: Physiological Parametersmentioning
confidence: 80%
See 3 more Smart Citations